Thin calcification (< 2 mm) can highly predict intraplaque hemorrhage in carotid plaque: the clinical significance of calcification types - Kashiwazaki, Daina; Yamamoto, Shusuke; Hori, Emiko; Akioka, Naoki; Noguchi, Kyo; Kuroda, Satoshi (Acta neurochirurgica, 2022)
Purpose Calcification pathogenesis and the relationship between calcification and plaque composition remain unclear. This study explored the calcification characteristics of vulnerable plaques, especially focusing on calcification thickness, using computed tomography angiography and magnetic resonance plaque imaging. Methods Demographic, computed tomography angiography, and magnetic resonance plaque imaging data were acquired from 178 patients with 229 lesions diagnosed with carotid stenosis. The calcification types were categorized by calcification thickness. We evaluated their features, including the anatomical location and the plaque composition compared with MR plaque imaging, and clarify the clinical characteristics. Furthermore, an immunohistochemical subgroup analysis was performed on 84 lesions treated with carotid endarterectomy. Results The result of the ROC analysis suggested the threshold between symptomatic and asymptomatic calcification was 2.04 mm (AUC;0.841, 95%CI; 0.771–0.894). Calcification with ≥ 2 mm thickness was classified as thick calcification and < 2 mm thickness as thin calcification. Multivariate analysis suggested the prevalence of symptomatic patients in the thin calcification group was significantly higher than others ( P = 0.01; odds ratio, 4.1; 95% confidence interval 2.8–7.2). Plaques with thin calcification were associated with plaque with intraplaque hemorrhage ( P < 0.01). The interobserver reliability ( κ ) of calcification type was 0.962 (95% confidence interval, 0.941–0.988). Immunohistochemical analysis demonstrated that the numbers of CD68-positive cells and CD31-positive microvessels in shoulder lesions were significantly higher in the thin calcification group than in the non-thin group (both P < 0.01). Conclusions Thin calcification was associated with plaques with intraplaque hemorrhage and had different clinical implications than thick calcification.